(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
In this article you will be given general information about the history of emergence of the Russian and Uzbek language, their advantages, both similarities and differences, as well as folk art and its example, language learning opportunities are written.